Translation and Intercultural Education - Pascua, Isabel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThis paper deals with translated Canadian multicultural literature written for children and its reception in an intercultural education context in Spanish schools. In the first part of the paper I will introduce intercultural education. In the second part, I will examine the role of the translator working in a multicultural environment where texts are written in one language (English) in one country (Canada), then translated into another language (Spanish) and published in Spain. I will also look at the reception of these translations as well as the strategies translators should use to maintain the otherness of the original texts.